Interactive Media for Increasing Logical-Mathematical Intelligences in Differentiated Instruction Practice - Sofia, Ari; Syafrudin, Ulwan; Yulistia, Annisa (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Logical mathematical intelligence is important to be trained from an early age in the demands of 21st century competencies, because it is related to problem-solving ability, a logical thinking, and numerical processing skills in daily life practices of early children. One alternative way to increase this intelligence is to use interactive media as a practice of digitalization and differentiated instruction in learning activities. Based on the problem, this study aims to increase the logical-mathematical intelligence of early childhood through the implementation of interactive media in learning activities. This research method used pre-experiment design in the form of one group pre-test and post-test. The sample in this study were children aged 5-6 years with a total of 21 children. Data collection instruments using logical mathematical intelligence observation sheets. Data analysis techniques using paired sample t-test. The result of the data analysis showed that the Sig. (2 tailed) of 0,000 < 0,05. Thus, there is an effect of implementing interactive media to improve logical-mathematical intelligence in early childhood learning by using differentiated learning practices.